(untitled) (Sustainability in Debate, 2016)
This article discusses the floral extraction in Brazil’s Amazon region, based on the collection of jaborandi leaves in the area of Carajás (Pará, Brazil). This plant contains pilocarpine, used in the production of eye drops applied in the treatment of glaucoma. The texts seeks to analyze and theorize about the complex and multiple factors that determine the replacement, or not, of floral extraction by cultivation. It was found that the stabilization of the national and international demand for pilocarpine is allowing the coexistence plant cultivation with extraction. Research also showed that one of the leading companies in the pilocarpine extraction and exports employs a strategy to add a positive image to its activities resulting from its partnerships with extractive communities in Pará and other areas where jaborandi occurs as a native plant.